Tropical forests : regional paths of destruction and regeneration in the late twentieth century - Rudel, Thomas K. (New York : Columbia University Press, 2005)
In Tropical Forests, Rudel analyzes hundreds of local studies from the past twenty years to develop a much-needed, global perspective on deforestation. With separate chapters on individual regions, including South and Central America, the Caribbean, and Africa, Rudel's work offers an up-to-date assessment of the world's tropical forests. In the concluding chapter, Rudel considers the implications of these trends and describes policy directions for conserving biodiversity and promoting sustainable development in each region.
9. Southeast Asia: Deforesting the Lowlands, Afforesting the Highlands10. Through a Regional Lens: Conservation Policies in Large and Small Forests; Appendix: Case Studies and Accompanying QCAs for Each Region; Notes; References; Index.
Includes bibliographical references (pages 195-220).
Print version record.
JSTOR
Keywords: Deforestation -- Tropics; Rain forest conservation; Déboisement -- Régions tropicales; Forêts pluviales -- Conservation; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; SCIENCE -- Life Sciences -- Ecology; Deforestation; Rain forest conservation; Tropics